Injuries across a pre-professional ballet and contemporary dance tertiary training program: A retrospective cohort study - Fuller, M.; Moyle, G. M.; Minett, G. M. (Journal of Science and Medicine in Sport, 2020)
Objectives: The study aims to analyse the incidence of medical attention injuries, subsequent injuries, and the median time to injury, across tertiary ballet and contemporary dance training programs. Design: Retrospective cohort. Methods: Consenting ballet and contemporary dance students completing the third/final year of two tertiary programs were included. The three-year programs consisted of six semesters. Access was granted to onsite physiotherapy notes, timetables, and academic enrolment. Injury was defined as requiring medical attention. Injury and exposure data were extracted, injuries coded for location and tissue, and subsequent injuries, occurring after an initial index injury, categorised. Mean, standard deviation, range, injury incidence, risk and rate ratios, proportions and Kaplan-Meier curves were calculated to report participant characteristics, and injury patterns across three years of the dance program. Results: All 17 students (mean age = 20.7 years; standard deviation = 1.32) from one program consented to participate, of which all were injured across the three-year program, with 2.71 (95% confidence interval: 2.22, 3.20) injury incidence rate per 1000 h, and increasing injury incidences seen across the program. The most injured site and tissue were the ankle (17.65%) and muscle (23.53%) respectively. 74.86% of subsequent injuries were different (affecting a different location and tissue), and 4.88% reinjuries (affecting the same location, tissue, and structure after recovery). The median time to the first injury was seven weeks in the first semester, and later in subsequent year levels. Conclusions: Increasing injury incidences were seen across the program. Most subsequent injuries were different from previous injuries in this cohort. Future research should use exposure measures beyond hours (i.e. intensity) and consider subsequent injuries.